2016
DOI: 10.1002/9780470942390.mo150122
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Imaging in Mice

Abstract: The mouse is the mammalian model of choice for investigating cardiovascular biology, given our ability to manipulate it by genetic, pharmacologic, mechanical, and environmental means. Imaging is an important approach to phenotyping both function and structure of cardiac and vascular components. This review details commonly used imaging approaches, with a focus on echocardiography and magnetic resonance imaging and brief overviews of other imaging modalities. We also briefly outline emerging imaging approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 113 publications
0
17
0
Order By: Relevance
“…Mouse models are an alternative, but it is challenging to create consistent MIs in mice; and their smaller size relative to rats pose additional difficulties for imaging studies (higher heart rates, much smaller size, etc.) [ 14 ]. To address these limitations, we investigated the specific conditions which could enable creation of a murine (rat) model of hemorrhagic MI.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse models are an alternative, but it is challenging to create consistent MIs in mice; and their smaller size relative to rats pose additional difficulties for imaging studies (higher heart rates, much smaller size, etc.) [ 14 ]. To address these limitations, we investigated the specific conditions which could enable creation of a murine (rat) model of hemorrhagic MI.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The majority of the immunized animals then develop a CD4+ cell-mediated experimental autoimmune myocarditis (EAM) peaking 21 days after the first immunization, despite no apparent clinical symptoms of heart failure. 11 Since echocardiographic parameters, such as LV systolic function, have been used as outcome parameters for interventional studies in EAM before, and previous studies reported diverging echocardiographic findings in this setting, we performed serial TTE examinations throughout the course of the disease to establish imaging standards and reference values for future examiners. 9,10 To improve the feasibility of the examination, TTE is frequently conducted under continuous anaesthesia (eg with isoflurane), which can affect haemodynamics and LV systolic function.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, close monitoring of the depth of anaesthesia is essential to obtain valid and reliable results. 11 Since echocardiographic parameters, such as LV systolic function, have been used as outcome parameters for interventional studies in EAM before, and previous studies reported diverging echocardiographic findings in this setting, we performed serial TTE examinations throughout the course of the disease to establish imaging standards and reference values for future examiners.…”
Section: Introductionmentioning
confidence: 99%
“…Additional reagents and equipment for assessing titer of bacteria (Elbing and Brent, 2002), isoflurane anesthesia of mice (Phoon and Turnbull, 2016), injection of mice (Donovan and Brown, 2006a), and euthanasia of mice by CO 2 asphyxiation (Donovan and Brown, 2006b) Preparation of mouse NTHi inoculum 1. Grow NTHi overnight at 37°C in a 5% CO 2 atmosphere on sBHI agar.…”
Section: Methodsmentioning
confidence: 99%
“…2. Anesthetize mice aged 8 weeks with isoflurane (Phoon and Turnbull, 2016) and inoculate intranasally by applying 10 µl of bacterial suspension to each nostril (10 8 cfu in 20-µl total volume; see Basic Protocol 1, step 5).…”
Section: Methodsmentioning
confidence: 99%